1992
DOI: 10.1044/jshr.3504.892
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Processing Dynamic Information to Identify Vowel Quality

Abstract: This study examined age-related differences in the use of dynamic acoustic information (in the form of formant transitions) to identify vowel quality in CVCs. Two versions of 61 naturally produced, commonly occurring, monosyllabic English words were created: a control version (the unmodified whole word) and a silent-center version (in which approximately 62% of the medial vowel was replaced by silence). A group of normal-hearing young adults (19–25 years old) and older adults (61–75 years old) identified these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(50 reference statements)
1
14
1
Order By: Relevance
“…On the other hand, EHI listeners were expected to benefit more from steady-state information compared to transition cues, based on age-related deficits in using dynamic cues discussed by Fox et al ͑1992͒. No significant disadvantages to use four subsegmental cues was shown for our EHI participants, although we note that the high variability in EHI listener performance may have obscured possible subsegmental condition effects in this study.…”
Section: B Intelligibility Of Interrupted Speech Of Young and Older contrasting
confidence: 46%
See 1 more Smart Citation
“…On the other hand, EHI listeners were expected to benefit more from steady-state information compared to transition cues, based on age-related deficits in using dynamic cues discussed by Fox et al ͑1992͒. No significant disadvantages to use four subsegmental cues was shown for our EHI participants, although we note that the high variability in EHI listener performance may have obscured possible subsegmental condition effects in this study.…”
Section: B Intelligibility Of Interrupted Speech Of Young and Older contrasting
confidence: 46%
“…Fox et al ͑1992͒ reported an age-related decrement in the ability to use dynamic cues in CVC margins for vowel and consonant perception among various age groups with relatively normal hearing, supporting age-related deficit hypothesis. Ohde and Abou-Khalil ͑2001͒, however, found the similar abilities among young, middle-aged, and older adults who had near-normal hearing for their age ͑i.e., less than 40 dB HL at 4000 Hz in older adults͒ to use these dynamic formant transition cues for vowel and consonant perception, thereby not supporting age-related deficits in using dynamic cues.…”
Section: Introductionmentioning
confidence: 61%
“…There remains some possibility that reduced hearing sensitivity among ONH listeners contributed to their relatively poorer performance for shorter CO stimuli; however, correlations between hearing sensitivity and performance did not reach significance in our subject sample. Fox et al (1992) reported that ONH listeners achieved lower word recognition scores than YNH listeners when vowel centers were removed from CVC monosyllables. However, the performance difference between their groups was only 7.2 percentage points (85.3% for YNH listeners vs. 78.1% for ONH listeners).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that aging preferentially reduces the ability to process rapidly-changing cues to vowel identification, suggesting that older listeners may rely more strongly on quasi steady-state cues located in the vowel centers than on formant transitions located in the vowel edges (Dorman et al, 1985;Elliott et al, 1989, Fox et al, 1992although cf. Ohde and Abou-Khalil, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and electrophysiological studies in humans with presbycusis show increased detection thresholds for FM signals, increased difficulty in processing rapidly changing acoustic cues, and reduced temporal precision of neural responses to speech syllables (Anderson et al 2012;Buss et al 2004;Dorman et al 1985;Elliott et al 1989;Ernst and Moore 2012;Fox et al 1992;Gordon-Salant et al 2007;Lacher-Fougere and Demany 1998;Tremblay et al 2003). Our data provide electrophysiological markers for two prominent theories that may explain such deficits: the noisy processing and speed of processing theories (Mahncke et al 2006a(Mahncke et al , 2006bSalthouse 1996).…”
Section: Discussionmentioning
confidence: 72%